Cash Waqf Linked Sukuk Through Securities Crowdfunding in Indonesia - Imtiyaz Wizni Aufa; Anugrah Muhtarom Pratama; Umi Khaerah Pati (Jambura Law Review, 2023)
Islamic charitable innovations have evolved to give rise to the integration between Sukuk and cash waqf called Cash Waqf Linked Sukuk (CWLS). The integration of these two things is promising when combined, considering that Sukuk has long been named a commercial sharia instrument that aims to raise funds, while cash waqf as a sharia social instrument has played a philanthropic role. As for Indonesia, The cash waqf combined with Sukuk has become a new fiscal instrument because it has advantages in addition to contributing to development, furthermore, the returns obtained are reused into waqf money for socio-economic projects and funds invested be returned at maturity. As a legal research, this article uses qualitative analysis with statutory approaches and conceptual approaches. This article intends to introduce a new conceptual framework model innovation between CWLS and fintech types of Islamic securities crowdfunding. This innovation is for no reason considering that the use of fintech types of Islamic securities crowdfunding makes CWLS more popular and more flexible so that the funds raised are expected to be larger and can reach the broader community for the construction of more massive socio-economic projects. Furthermore, this article provides an overview of the proposed innovations in achieving the goals of maqasid al-shariah, regulations, and opportunities and challenges to be implemented in Indonesia.